Screening for probiotic properties and potential immunogenic effects of lactobacilli strains isolated from various food products - Kowalczyk, Magdalena; Radziwill-Bienkowska, Joanna M.; Marć, Małgorzata A.; Jastrząb, Rafał; Mytych, Jennifer; Siedlecki, Paweł; Szczepankowska, Agnieszka K. (Frontiers in Microbiology, 2024)
Introduction Deceleration of disease progression and re-establishment of microbial balance in the gut is often achieved by application of lactobacilli strains. Their beneficial effects are associated with probiotic properties, which may be accompanied by immunomodulatory action at mucosal surfaces. Methods To single out such strains, we screened almost three hundred lactobacilli isolates from eight genera and various food sources for acid and bile salt tolerance, adhesion to mucin as well as hemolytic activity and antibiotic susceptibility. Moreover, the immunomodulatory effects of cell-free supernatant (CFS) fractions of five lactobacilli strains were assessed using an in vitro cell line model. Results and discussion By our rationalized selection approach, we identified thirty-five strains with probiotic potential and biosafety features. Additionally, we showed that CFS from the Lactiplantibacillus L_4 strain downregulates proinflammatory cytokines IL-8 and IL-1β. In contrast, IL-8 expression was found to increase after treatment with CFSs of Lactiplantibacillus L_2 and L_5 and IL-1β was upregulated by CFSs of Lactiplantibacillus L_1 and Lactiplantibacillus L_3. Overall, our result delineate a rational approach of selecting lactobacilli strains for probiotic development to support the gut microbiota equilibrium and reinforce the host immune system.